Kradzieże samochodów w Polsce jako element ryzyka w ubezpieczeniach auto casco - Wieteska, Stanisław (Annales. Etyka w Życiu Gospodarczym, 2015)
The problem of car theft has been observed for many years. The largest scale of this phenomenon occurred in the 1990’s. In this paper, the issue is discussed in social, ethical and economic aspects. We present the scale of the phenomenon of the theft of passenger vehicles in Poland in the years 2001–2012 in terms of the number of vehicles, type of stolen vehicles and the accident areas. In addition, we present the cause of theft and selected ways to protect cars from it. We also briefly discuss the role and responsibility of the insurance companies.